Transformasi Tubuh Dan Resistensi Dalam Novel Cantik Itu Luka Dan Metamorphosis : Sebuah Kajian Intertekstual - Priyono, Akbar; Gunawan, Ayub; Lapasau, Merry; Megawati, Erna; Sari, Vina Nur Indah (Jurnal Ragam Pengabdian, 2026)
This study aims to describe and compare the forms of bodily transformation, the social function of metamorphosis, and the representation of family alienation as a structure of power in Eka Kurniawan's novel Cantik Itu Luka and Franz Kafka's Metamorphosis. Both novels employ grotesque and surreal elements to critique different power systems: Kafka critiques capitalism and bureaucracy in early 20th-century European modern society, while Kurniawan critiques patriarchy and colonialism in the postcolonial Indonesian context. Using a qualitative descriptive-comparative method with an intertextual approach, this study analyzed primary data in the form of quotations from both novels and secondary data from relevant scholarly articles. The analytical techniques included close reading, comparative matrices, and critical analysis employing three theoretical frameworks: deconstruction, postcolonial feminism, and existentialist absurdism. The findings reveal that: (1) the physical forms of transformation differ between the two novels but are functionally similar as markers of lost social status; (2) the social function of metamorphosis in Kafka serves as a critique of capitalism that reduces human beings to their economic productivity, while in Kurniawan it critiques patriarchy and colonialism that commodify women's bodies; (3) family in both novels is represented not as a place of protection but as an extension of repressive power systems. This research contributes to the development of comparative literature studies by offering an integrative model combining three theoretical frameworks.